Elements of Expectancy: Incorporating the Student Voice in the Online Design Process - Holley, Debbie; Andrew, David; Cook, John; Celik, Cevrem; Mitchell, Andy (Proceedings of the International Conference on Networked Learning, 2006)
Designing learning technologies, however interactive they are, is a front-loaded activity with limited opportunity for adapting to the student response in their design. This paper explores the involvement of the student voice in the design of learning objects, and explores the issues involved in collaborative working in the process.